Notes on Scottish Curing-Stones and Amulets (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author discusses the intersection of magic, superstition and medicine from written records in Antiquity to the superstitions still practiced in Scotland in the nineteenth century. Most of the article is dedicated to the discussion of items such as stones or charms that were believed to cure disease in humans and livestock. Several examples associated with famous Scots were borrowed and exhibited on the day and some of the artefacts in the Society’s museum are also mentioned.